KEY ASPECTS OF NATURAL LANGUAGE PROCESSING - Парнус, Катерина; Давидович, Марина; Хорош, Ольга (SWorldJournal, 2023)
Natural Language Processing (NLP) is a field of artificial intelligence that focuses on enabling computers to understand, interpret, and generate human language in a way that is both meaningful and useful. NLP plays a crucial role in various applications,